44th Conference - FOUNDATION ENGINEERING Brno 2016 - Editorial Foreword (Acta Polytechnica CTU Proceedings, 2017)
Organized by: Czech Geotechnical Society of the Czech Institution of Civil Engnineers together with Czech Technical University in Prague The traditional yearly conference of Foundation Engineering Brno is organized by the Czech Geotechnical Society. This is the largest annual event in the field, where researches, academicians, designers, investors and contractors present, share and discuss the results of their research and share their experiences with each other. Each year is focused on a certain topical subject. Selected experts from abroad are invited for Keynote lecture for each conference. This issue of Acta Polytechnica Proceedings includes selected scientific papers that were presented at the 44th Conference of the Foundation Engineering held in Brno in 2016. The focus of this conference was Ground Improvement. The scientific program was divided into five sections: 1. Geotechnical investigation 2. Ground improvement for Earth structures 3. Ground improvement for Foundation structures 4. Ground improvement for Underground structures 5. Significant geotechnical structures realized in the Czech Republic and abroad Editor: Daniel Jirásko Scientific comittee: Jiří Barták, Taťana Holoušová, Josef Jettmar, Jan Masopust, Ivan Vaníček, Czech Technical University in Prague, Czech Republic Petr Nosek, Michael Remeš, Foundation Engineering company, Czech Republic Eva Hrubešová, TU Ostrava, Czech Republic Ivan Slávik, Peter Turček, Mária Masarovičová, STU Bratislava, Slovak Republic Jindřich Řičica, EFFC, UK Lubomír Klímek, Geotest, Brno, Czech Republic Lubomír Miča, Kamila Weiglová, Brno University of Technology, Czech Republic Petr Svoboda, Keller-Special Foundation Local organizing comittee: Ivan Vaníček, Daniel Jirásko, Josef Jettmar, Jiří Barták, Taťana Holoušová, Michael Remeš Guarantor of the peer review proces: Jiří Barták, Jan Masopust, Daniel Jirásko, Jan Kos, Michael Remeš Guarantor of language editing: Czech Geotechnical Society, cooperation with Hana Horká and Renáta Nivenová